Relationship between Scrotal Circumference and Quality of Semen Production in Bulls: A Meta-Analysis Review - Ikwan Wahyudi; Moh. Qalfin; R. Susanti; Talitha Widiatningrum (Jurnal Sain Peternakan Indonesia, 2022)
This meta-analysis review was conducted to determine the relationship between scrotal circumference and semen production quality in bulls. The research method includes article search, selection, and assessment stages based on the specified inclusion criteria. The results of the selection and assessment of articles obtained 38 articles for meta-analysis. Data analysis was performed using the CMA program using a random-effects model to estimate the correlation coefficient. The results of the meta-analysis showed that overall scrotal circumference was significantly correlated (p < 0.05) with semen volume (r = 0.441), semen concentration (r = 0.328), and spermatozoa motility (r = 0.411). The relationship between scrotal circumference and semen quality was positive in the moderate category. Analysis based on the variation of bull breeds showed that the relationship between scrotal circumference and semen volume and concentration was not significantly different in Bos taurus, Bos indicus, and Bos sondaicus cattle (p > 0.05). Scrotal circumference and spermatozoa motility were significantly different in the Bos taurus, Bos indicus, and Bos sondaicus cattle (p < 0.05). This meta-analysis confirms that scrotal circumference can be a parameter in determining superior bulls because the scrotal circumference is positively related to the quality of semen production.